2016
DOI: 10.1002/dac.3163
|View full text |Cite
|
Sign up to set email alerts
|

Parallel checking of content integrity in multi‐cloud storage of heterogeneous sensor systems

Abstract: Heterogeneous sensor systems collect a large amount of sensor data. Because of limited processing capability of sensor nodes, such data are typically stored and processed in a centralized environment in the cloud. However, when data are managed and processed by multiple cloud servers, users do not physically possess these data. The risk of unauthorized access to the cloud data increases dramatically. Therefore, enforcing the integrity of the outsourced data remotely becomes a challenge in the heterogeneous sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
(103 reference statements)
0
3
0
Order By: Relevance
“…The experimental result reveals that the framework can help in the improvement of throughput and the reduction of transmission delay. Mao et al introduced a framework for a multi-cloud environment named parallel cloud data possession checking scheme [26]. The proposed framework uses a homomorphic verification tag that is generated by a pallier cryptosystem to support unlimited query challenges with support for error localization and data correction.…”
Section: B Rq2:what Are the Contributions Been Proposed By The Selecmentioning
confidence: 99%
“…The experimental result reveals that the framework can help in the improvement of throughput and the reduction of transmission delay. Mao et al introduced a framework for a multi-cloud environment named parallel cloud data possession checking scheme [26]. The proposed framework uses a homomorphic verification tag that is generated by a pallier cryptosystem to support unlimited query challenges with support for error localization and data correction.…”
Section: B Rq2:what Are the Contributions Been Proposed By The Selecmentioning
confidence: 99%
“…The experimental result reveals that the framework can help in the improvement of throughput and the reduction of transmission delay. Mao et al introduced a framework for a multi-cloud environment named parallel cloud data possession checking scheme [25]. The proposed framework uses a homomorphic verification tag that is generated by a pallier cryptosystem to support unlimited query challenges with support for error localization and data correction.…”
Section: B Rq2:what Are the Contributions Been Proposed By The Selecmentioning
confidence: 99%
“…Furthermore, Liang et al also used Theoretical analysis and Simulation combined for evaluation [42]. And lastly, Mao et al also used two evaluation mechanisms for evaluating their proposals [25]. Hence, any study that did not use any evaluation mechanism or did not evaluate a given work, we categorized such study as "None" (as shown in Table 8).…”
Section: Rq3:what Are the Existing Evaluation Mechanisms Used By Tmentioning
confidence: 99%